Effects of a Teacher Development Program on Science Teachers’ Conceptions of Inquiry-based Teaching and Teaching Quality - Soonjan, Jannapha; kaewkhong, Kreetha (Science Essence Journal, 2022)
This research explores the conceptual change of inquiry-based teaching and the teaching quality of 12 Thai elementary science teachers who participated in a teacher professional development program. We developed the teacher professional development program focusing on helping teachers understand how to teach science using inquiry-based methods. The 12 volunteer Thai elementary science teachers were asked to participate in the program which consisted of 15 activities based on the five essential features of inquiry teaching. Each activity had a specific objective, the teachers were trained by doing activities designed by considering the five essential features of inquiry teaching. The teachers ‘conceptions of inquiry-based teaching were investigated at the beginning and finishing of the workshop by 18 open-ended questions on teaching scenarios developed by researchers. Besides, their lesson plans and teaching video clips were also determined with the Science Teacher Inquiry Rubric (STIR) to indicate teaching quality and level of inquiry. From the results, we found that teachers’ conceptions of inquiry-based teaching were significantly correlated to their teaching quality.